Legal Protection Analysis Of Maria Cave As a Spiritual Tourism - Sudarmanto, Hery Lilik (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
The tourism potential in Indonesia is very significant. However, based on the phenomenon that occurs in several tourist destinations around the world it is found that many tourist attractions are especially damaged in Indonesia due to irresponsible actions. The purpose of this study was to reveal the legal protection of one of the tourist attractions in Indonesia, Maria Cave as a spiritual tourism destination in the City of Kediri. The study was conducted based on research methods using normative jurisdiction review. The results of the study revealed that so far the legal protection of spiritual tourism has been supported by the government but concretely has not been found in the Kadiri city government regulations. Therefore, to minimize the existence of activities that can cause damage and forms of protection of existing tourist destinations, it is necessary to specifically make government and local government regulations as well as to supervise and impose strict sanctions on all forms of irresponsible actions which are certainly supported by a budget enough when using technology for sustainable tourism. Both the community, tourists and entrepreneurs have their respective obligations that must be obeyed in accordance with the provisions and laws in force in Indonesia.